The Significant Association Between Maternal Anemia and the Incidence of Neonatal Asphyxia in Indonesia - Ulil Albab Habibah; Cinta Putri Aulia Nugroho; Muhammad Rio Al Faridzky; Muhammad Halymtar Farrel Assyidiqi; Satria Akbar Putra Asmara (Jurnal Penelitian Kesehatan SUARA FORIKES, 2026)
Asphyxia is a condition in which a newborn fails to breathe spontaneously and regularly. According to the Ministry of Health in 2017, neonatal mortality caused by asphyxia reached 27.8%. One of the causes of neonatal asphyxia is anemia gravidarum. This process begins with decreased hemoglobin (Hb) levels, impaired oxygen transport, and eventually leads to fetal hypoxia. This literature review was conducted in March 2026. Literature searches were performed using Google Scholar, PubMed, ScienceDirect, and Garuda, with a publication range from 2016 to 2026. Article selection was carried out following PRISMA guidelines. Five studies showed a significant association between neonatal asphyxia and anemia gravidarum, while one study showed no significant association. Therefore, healthcare professionals are expected to provide education regarding nutritional intake for pregnant women as a preventive measure against anemia and to emphasize the importance of antenatal care.Keywords: anemia gravidarum; asphyxia; indonesia